PENGELOLAAN SAMPAH RUMAH TANGGA” DI DESA TRIYAGAN KECAMATAN MOJOLABAN KABUPATEN SUKOHARJO - Nur Hidayati; Nony Puspawati; Mardiyono Mardiyono; Soebiyanto Soebiyanto (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
The role of the community in waste management at this time is generally limited to waste disposal. We are not yet at the stage of waste management where waste can be reused by the community. Waste management must be handled comprehensively with the 3R principle, namely reduce, namely reducing waste piles; reuse by reusing waste that is not used; and recycle, namely recycling into products of economic value. Good waste management is expected to reduce the volume of waste that is disposed of at the final disposal site (TPA). The need for community education on proper waste management and disposal in order to reduce the impact of environmental pollution.The service was carried out in Triyagan Village, Mojolaban District, Sukoharjo Regency, at the beginning of the activity by giving a pre-test, presenting the material, and at the end of the activity, namely an evaluation with a post-test. The results of the pre-test mean score are 62, and the post-test average score is 82, after receiving counseling. The score of the evaluation results showed that there was a positive change in the mindset of the community.